Single-cell RNA sequencing reveals time- and sex-specific responses of mouse spinal cord microglia to peripheral nerve injury and links ApoE to chronic pain - Tansley, Shannon; Uttam, Sonali; Ureña Guzmán, Alba; Yaqubi, Moein; Pacis, Alain; Parisien, Marc; Deamond, Haley; Wong, Calvin; Rabau, Oded; Brown, Nicole; Haglund, Lisbet; Ouellet, Jean; et al. (Nature communications, 2022)
Activation of microglia in the spinal cord following peripheral nerve injury is critical for the development of long-lasting pain hypersensitivity. However, it remains unclear whether distinct microglia subpopulations or states contribute to different stages of pain development and maintenance. Using single-cell RNA-sequencing, we show that peripheral nerve injury induces the generation of a male-specific inflammatory microglia subtype, and demonstrate increased proliferation of microglia in male as compared to female mice. We also show time- and sex-specific transcriptional changes in different microglial subpopulations following peripheral nerve injury. Apolipoprotein E ( Apoe ) is the top upregulated gene in spinal cord microglia at chronic time points after peripheral nerve injury in mice. Furthermore, polymorphisms in the APOE gene in humans are associated with chronic pain. Single-cell RNA sequencing analysis of human spinal cord microglia reveals a subpopulation with a disease-related transcriptional signature. Our data provide a detailed analysis of transcriptional states of mouse and human spinal cord microglia, and identify a link between ApoE and chronic pain in humans. Microglia subpopulations may differentially contribute to pain. Here, the authors show that peripheral nerve injury induces time- and sex-specific transcriptional changes in mouse spinal cord microglia subpopulations and that ApoE is linked to neuropathic pain hypersensitivity in mice and humans.